p(x)=x^3+6x^2+12x+16 com p(x-1)?

1 Resposta

Classificação
  • Anônimo
    Há 5 meses

    P(x) = x³ + 6x² + 12x + 16

    P(x - 1) = (x - 1)³ + 6. (x - 1)² + 12 . (x - 1) + 16

    (a + b)³ = a³ + 3a²b + 3ab² + b³

    (x - 1)³ = x³ + 3x² . (-1) + 3x . (-1)² + (-1)³ = x³ - 3x² + 3x - 1

    (a + b)² = a² + 2ab + b²

    (x - 1)² = x² + 2x . (-1) + (-1)² = x² - 2x + 1

    P(x - 1) = x³ - 3x² + 3x - 1 + 6x² - 12x + 6 + 12x - 12 + 16

    P(x - 1) = x³ + 3x² + 3x + 9

Tem mais perguntas? Obtenha suas respostas perguntando agora.